First Report on The Naturalized Alocasia cucullata (Araceae) in Java, Indonesia - Arifin Surya Dwipa Irsyam; Muhammad Rifqi Hariri; Asih Perwita Dewi; Rina Ratnasih Irwanto (Journal of Tropical Biodiversity and Biotechnology, 2023)
The presence of naturalized Alocasia cucullata (Lour.) G.Don (Araceae) in Java is reported for the first time in this paper. The species is an introduced ornamental plant native to India, Sri Lanka, and Indo-China and was only known in cultivation. In this study we collected samples from its naturalized populations in Sukabumi Regency (Cibadak Subdistrict), Sumedang Regency (Jatinangor and Tanjungsari Subdistrict). The observed population grows along the roadside, coastal, ITB Jatinangor green space area, and palm oil plantation. In nature, A. cucullata may spread vegetatively either through root suckers, corms, and stem fragments. The description, distribution map, photographs, and a brief discussion are provided here.